KEPEMIMPINAN PEREMPUAN DALAM PERSPEKTIF ISLAM - Himmah, Dhurotun Nasicha Aliyatul; Yaqien, Nurul (J-MPI (Jurnal Manajemen Pendidikan Islam), 2017)
Women's leadership has always been a discussion of controversy, especially in explaining, interpreting and determining the law of a woman's leadership. This study aims to: (1) Review the interpretation related to the concept of leadership with the interpretation model of maudhu'i Al-Qur'an letter An-Nisa verse 34 and Al-Mujadalah verse 11 according to some classical and contemporary commentators including Ibn Abbas, Imam Jalaludin, Ibn Kathir, Mustafa Al-Maraghi, Muhammad Hasbi and Quraish Shihab, (2) Assessing the relevance of the concept of female leadership in an Islamic perspective with the concept of leadership in the 21st century. This type of research is literature study using descriptive-analytic method, historical-philosophical approach, carried out with documentation techniques, analysis, interpretation, checking the validity of the data to obtain the results of the study according to purpose. The results of the study show that there are differences between the thoughts of classical mufassir and contemporary mufassir on women's leadership based on An-Nisa verse 34. It is the differences in times, conditions, situations and civilizations that influence it. The 21st Century is no longer a century where women cannot join in politics, government, social affairs, education, and so on. Contemporary mufassir allow women to be leaders as long as they do not violate the sharia and do not ignore the main task of being a wife. Relevance is related to the realization of the Constitution of 1945 article 27 concerning equal rights and obligations of Indonesian citizens, and Article 31 related to the right of education for all citizens of Indonesia relevant to the letter of Al-Mujadalah verse 11. The relevance is related to the realization of Article 27 of the 1945 constitution concerning the equality of Indonesian citizens' rights and obligations, and Article 31 concerning the right of education of all Indonesian citizens relevant to Al-Mujadalah verse 11. Men or women who are leaders, most importantly is the realization of the good leadership for creating baldatun thayyibun warabbun ghafur.